Influence of deficit irrigation and biochar amendment on growth, physiology, and yield of cucumber in West Texas - Arjun Kafle; Sukhbir Singh; Manpreet Singh; Preetaman Bajwa; Sanjit Deb; Catherine Simpson; Glen Ritchie (Scientific Reports)
Abstract Despite growing interest in adopting water-conserving strategies such as deficit irrigation (DI) and biochar amendment in arid and semi-arid regions, there are remarkably few studies conducted on the integration of these two strategies in water limited West Texas region. The aim of this study was to assess the interactive effects of DI and biochar amendment on saturated hydraulic conductivity of soil and the growth, physiology and yield of cucumber (Cucumis sativus) in West Texas. A split-plot design was used to randomize four irrigation treatments (with two levels before and after mid-season) as the main plot [I1: 100% crop evapotranspiration (ETc)-100% ETc, I2: 80% ETc-60% ETc, I3: 60% ETc-80% ETc, I4: 40% ETc-40% ETc] and three biochar rates as subplot [0 t/ha, 15 t/ha, and 20 t/ha] with four replications. Irrigation level I4 negatively impacted chlorophyll content, stomatal conductance, transpiration, photosynthesis, and intrinsic water use efficiency (iWUE) when the weather was hot and dry in 2022 compared to other treatments. Leaf area index (LAI) under I4 declined significantly by 52% and the final dry biomass by 47% compared to I1 across two years, although I3 reduced biomass by 17% only in 2022. As compared to I1, the yield penalties due to water stress in I2, I3, and I4 were 14, 16, and 34%, respectively, across two years. Although biochar rates 15 t/ha and 20 t/ha significantly increased the saturated hydraulic conductivity of soil by 1.6 and 2.2 folds in 2022 compared to the unamended control but biochar’s impact on cucumber growth, physiology, and yield was minimum during both years. Hence, our findings suggest that I2 can be adopted as an alternative to full irrigation which requires 25% less water and has 14% narrow yield gap. Biochar studies are needed to assess whether added biochar has an apparent long-term effect on improving cucumber yield.